Food allergen‐sensitized CCR9+ lymphocytes enhance airways allergic inflammation in mice. Issue 7 (20th February 2018) - Castan, L.; Cheminant, M.‐A.; Colas, L.; Brouard, S.; Magnan, A.; Bouchaud, G.
Abstract: Background: The mechanisms of the atopic march, characterized by a natural progression from food and cutaneous allergies to rhinitis and asthma, are still unknown. However, as several organs can be involved, chemokines and their receptors might be implicated in this process and may be instrumental factors. Objectives: We hypothesized that the T‐cell gut‐homing receptor CCR9 could be implicated in the evolution of allergic diseases. Methods: We characterized the immune response and the role of CCR9 in a murine model combining food allergy to wheat gliadin and a model of acute airways inflammation in response to house dust mite. Results: Compared with solely asthmatic‐like mice, we demonstrated that the aggravation of pulmonary symptoms in consecutive food and respiratory allergies, characterized by an increase in pulmonary resistance and a higher Th17/Treg ratio, was abrogated in CCR9 knockout mice. Moreover, transfer of food‐allergic CD4 + T cells from wild‐type but not from CCR9 −/− aggravated airways inflammation demonstrating that CCR9 is involved in food allergy‐enhanced allergic airway inflammation to unrelated allergens. Conclusion: Taken together, our results demonstrated a crucial role of the T‐cell homing receptor CCR9 in this model and validated its potential for use in the development of therapeutic strategies for allergic diseases.